Rejoinder to Giovanni Maltese - Richman, Naomi Irit ca. 20./21. Jh. (PentecoStudies, 2024)
In this brief rejoinder, I respond to Maltese’s three areas of questions. Taking the first two together, I explain that my use of verticality is not primarily a theological move but a theoretical one: attending to it reveals how the various structuralisms that pervade Christian ways of seeing the world are deeply entwined. In response to the third, I suggest that it is both possible and worthwhile to ascertain particularities of different cultural-religious perspectives in our work, so long as we also strive to problematize and historicize them at the same time.